Gender as an Impediment to Labor Market Success: Why Do Young Women Report Greater Harm? - Antecol, Heather; Kuhn, Peter (Journal of Labor Economics, 2000)
Compared to older women, young female job seekers are more than three times as likely to report that their ability to find a good new job is compromised by their gender. This phenomenon cannot be statistically attributed to observed personal or job characteristics, or to any “objective” measure of discrimination. Further, women's reports of gender‐induced advantage, and men's reports of gender‐induced harm, are also more prevalent among the young. A possible interpretation of all these patterns is that young people are more likely to interpret a given departure from gender‐neutral treatment as causally affected by their gender.